College students who endorse a sub‐threshold number of DSM‐5 alcohol use disorder criteria: Alcohol, tobacco, and illicit drug use in DSM‐5 diagnostic orphans. (15th March 2014) - Hagman, Brett T.; Cohn, Amy M.; Schonfeld, Lawrence; Moore, Kathleen; Barrett, Blake
<x xml:space="preserve">Abstract</x> Objectives Diagnostic orphans (DOs) represent a group of individuals with no formal diagnosis, despite endorsing some criteria of an alcohol use disorder (AUD). Prior research has indicated that rates of DSM‐IV DOs in college are high and closely resemble those with an alcohol abuse diagnosis across pertinent alcohol use risk factors. However, significant changes to the DSM‐IV AUD criteria have been made for the current DSM‐5 manual, which may impact how DOs are classified. This study examined the unique alcohol and illicit drug use characteristics of a group of 2, 620 DSM‐5 DOs in college and tested whether DOs differed from those with and without a DSM‐5 AUD across pertinent alcohol and drug use risk factors. Methods Participants were 2, 620 DSM‐5 DO undergraduate college students, between the ages of 18 and 30, recruited from three public universities in the Southeastern, United States. Results Diagnostic orphans represented 19.6% (n = 506) of the sample; with the most frequently endorsed criteria being tolerance and consuming alcohol in hazardous situations. DOs reported significantly greater alcohol consumption, alcohol and drug related problems, and illicit drug use compared to those with no DSM‐5 AUD diagnosis. Alternatively, DOs reported significantly lower alcohol use and illicit drug use compared to those with a DSM‐5 AUD. Conclusion The present findings indicate that DSM‐5 DOs in college represent a distinct group of drinkers relative to those with and without a DSM‐5 AUD. Current screening initiatives should target this group to prevent future escalation of problem drinking. (Am J Addict 2014;23:378–385)